2021
DOI: 10.1002/jnr.24973
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic circadian timekeeping properties of the thalamic lateral geniculate nucleus

Abstract: Benefits and risks of the outside world undergo dramatic daily changes governed by the light-dark (LD) cycle. Thus, most, if not all, living organisms developed biological clocks, which enable them not only to react to these cyclic events but also to predict them. In mammals, the central clock is localized in the suprachiasmatic nuclei (SCN) of the hypothalamus (Hastings et al., 2018(Hastings et al., , 2019. Its timekeeping properties are provided by clock cells maintaining a transcription-translation feedback… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…Though the pallidum is predominantly considered a motor region, a recent study reported that pallidal oscillations in local field potentials predicted sleep stages in patients with movement disorders providing evidence of its role in sleep 49 . Associations with thalamic GMV were not surprising since the thalamus is a key region for both sleep homeostatic and circadian time keeping 50,51 . Reduced volumes in the striatum have been linked to enhanced reward sensitivity, deficits in inhibitory control 52 and greater risk-taking 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Though the pallidum is predominantly considered a motor region, a recent study reported that pallidal oscillations in local field potentials predicted sleep stages in patients with movement disorders providing evidence of its role in sleep 49 . Associations with thalamic GMV were not surprising since the thalamus is a key region for both sleep homeostatic and circadian time keeping 50,51 . Reduced volumes in the striatum have been linked to enhanced reward sensitivity, deficits in inhibitory control 52 and greater risk-taking 53 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Berglund et al incorporated channelrhodopsin-2 with step-function mutations as the light-sensing opsin moiety and sbGluc as the light-emitting luciferase in a new luminopsin fusion protein, named step-function luminopsin (SFLMO), which has diversified the toolbox of bioluminescence optogenetic probes for bimodal control of neuromodulation for functional interrogation or therapeutic purposes [ 64 ]. Furthermore, scientists have also employed both the optogenetics approach and bioluminescence reporters to investigate mammalian circadian rhythms [ 89 , 90 , 91 ].…”
Section: Bioluminescence-induced Photoswitchable Protein-based Optica...mentioning
confidence: 99%
“…However, evidence accumulating over the last 2 decades questions the supremacy of the SCN ( Yoo et al, 2004 ; Guilding and Piggins, 2007 ; Paul et al, 2020 ). With the discovery of intrinsic clock gene expression in several extra-SCN brain nuclei, from the olfactory bulb ( Abraham, 2005 ), through thalamic ( Chrobok et al, 2021a ), epithalamic ( Guilding et al, 2010 ), hypothalamic ( Guilding et al, 2009 ) and midbrain regions ( Chrobok et al, 2021b ), all the way to the hindbrain ( Kaneko et al, 2009 ; Chrobok et al, 2020 ), it is now believed that at least a part of the rhythmic control of homeostasis must be devolved to such local clocks. These circadian timekeeping centres vary in the degree of their autonomy ( Guilding and Piggins, 2007 ; Paul et al, 2020 ; Chrobok et al, 2021c ).…”
Section: Introductionmentioning
confidence: 99%